1978
DOI: 10.1111/j.1432-1033.1978.tb12480.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human Blood Platelets with the 2′,3′‐Dialdehyde and 2′,3′‐Dialcohol Derivatives of Adenosine 5′‐Diphosphate and Adenosine 5′‐Triphosphate

Abstract: 1. The 2',3'-dialdehyde derivative of ADP (oADP) at concentrations approaching the millimolar range induces human blood platelets to undergo the transition from discoid to globular morphology (the 'shape change') but is incapable of inducing aggregation.2. When incubated with platelets for 1 min before addition of the agonist, oADP acts as a competitive inhibitor of shape change and aggregation induced by ADP. Under these conditions secretion and hence aggregation induced by low concentrations of collagen ; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…Rabbit platelet-rich plasma was prepared as described by Wallis (1978) using either acid citrate-dextrose (10 mm citrate) or 14.7 mM trisodium citrate as anti-coagulant. The aggregatory response was monitored and quantitated using a Payton Model 300 dual-channel aggregometer as described previously (Pearce et al, 1978). When studies were performed with methanolic solutions of drugs, the final concentration of methanol in the system never exceeded 2% (v/v) and control studies demonstrated that the concentration added had no effect on the observed response.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rabbit platelet-rich plasma was prepared as described by Wallis (1978) using either acid citrate-dextrose (10 mm citrate) or 14.7 mM trisodium citrate as anti-coagulant. The aggregatory response was monitored and quantitated using a Payton Model 300 dual-channel aggregometer as described previously (Pearce et al, 1978). When studies were performed with methanolic solutions of drugs, the final concentration of methanol in the system never exceeded 2% (v/v) and control studies demonstrated that the concentration added had no effect on the observed response.…”
Section: Methodsmentioning
confidence: 99%
“…Secretion by human platelets was estimated as described previously (Pearce et al, 1978) (Costa & Murphy, 1975). Secretion by rabbit platelets was estimated as described by Wallis (1978).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most of the studies this response was assessed by measurement of changes in the turbidity of the platelet suspension using a Payton dual channel aggregometer interfaced with a Rikadenki DBE-2 dual channel recorder (Born & Cross, 1963;Pearce et al, 1978). All additions were made simultaneously except where the effect of compounds was examined on the response to a non-saturating dose of ADP in which case the compound was added 15 s before ADP.…”
Section: Measurements Ofplatelet Aggregationmentioning
confidence: 99%